2022
DOI: 10.3390/ijerph192114511
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Behaviors and Information Sources during COVID-19 Pandemic: A Cross-Sectional Study in Japan

Abstract: Background: individual preventive behaviors are one of the key measures needed to prevent the spread of COVID-19. This study sought to identify the factors associated with the adoption of COVID-19 preventive measures, focusing specifically on information sources. Methods: we conducted a nationally representative cross-sectional survey of 30,053 Japanese adults in February 2021. The survey asked about socioeconomic, health-related, and psychological characteristics, attitudes toward immunization, and the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…HL and dimensions of access, understanding, appraisal, and application, significantly influenced COVID-19 PBs among VHVs and residents (except for access to HL). A higher HL level was associated with a higher COVID-19 PB score level, consistent with previous studies' findings (Silva and Santos 2021;Uchibori et al 2022). This might be because, in our study, 65.5% of VHVs had greater experience of more than 10 years, and 62.9% of the VHVs who served more than 10 households had adequate PBs.…”
Section: Factors Associated With Preventive Behaviors Regarding Covid-19supporting
confidence: 92%
“…HL and dimensions of access, understanding, appraisal, and application, significantly influenced COVID-19 PBs among VHVs and residents (except for access to HL). A higher HL level was associated with a higher COVID-19 PB score level, consistent with previous studies' findings (Silva and Santos 2021;Uchibori et al 2022). This might be because, in our study, 65.5% of VHVs had greater experience of more than 10 years, and 62.9% of the VHVs who served more than 10 households had adequate PBs.…”
Section: Factors Associated With Preventive Behaviors Regarding Covid-19supporting
confidence: 92%
“…The questionnaire comprised four major sections. Two authors [MM (specializing in risk science and environmental engineering) and SN (focusing on epidemiology and public health)] with expertise in risk perception and preventive behavior regarding COVID-19 (Adachi et al, 2022; Uchibori et al, 2022) were consulted to frame the questionnaire in the context of the COVID-19 pandemic. In the first section, prior to introducing any information on the infection status (covered in the second section), the participants rated their interest in COVID-19, changes in case numbers, their overall preventive behavior, mask usage, and attitudes toward vaccination using a five-point Likert scale (1 = strongly disagree to 5 = strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…Health insecurity, risk perception, and the resulting infection prevention behaviours in the midst of an infectious disease pandemic are greatly influenced by health literacy, which is created by information obtained from various sources, including the media and Internet (Taylor 2019). Furthermore, it has also been reported that risk perception and infection prevention behaviours regarding COVID-19 are associated with the availability of information sources (Adachi et al 2022;Lin et al 2020;Uchibori et al 2022). This suggests that several information sources are likely to shape beliefs regarding susceptibility to infection or infection control, rather than through hoaxes and conspiracy theories.…”
Section: Differences In Infection Prevention/risk-taking Behaviours R...mentioning
confidence: 99%
“…Furthermore, understanding these characteristics would be helpful in developing interactive risk communication tailored to relevant sub-groups. However, while previous studies have reported the factors associated with COVID-19 infection prevention behaviours, such as demographic factors (e.g., age, gender) (Muto et al 2020;Pampel et al 2010), sociodemographic factors (e.g., perception of infection risk, personality, and norms) (Bruine de Bruin & Bennett 2020; Nakayachi et al 2020;Qian & Yahara 2020), and knowledge and information sources (Batra et al 2021;Uchibori et al 2022), there have been no attempts to characterise such segments based on health literacy and beliefs regarding COVID-19 or to study the relationship between segments and infection prevention behaviour.…”
Section: Introductionmentioning
confidence: 99%